2012
DOI: 10.1593/neo.111436
|View full text |Cite
|
Sign up to set email alerts
|

ASC-J9 Suppresses Castration-Resistant Prostate Cancer Growth through Degradation of Full-length and Splice Variant Androgen Receptors

Abstract: Early studies suggested androgen receptor (AR) splice variants might contribute to the progression of prostate cancer (PCa) into castration resistance. However, the therapeutic strategy to target these AR splice variants still remains unresolved. Through tissue survey of tumors from the same patients before and after castration resistance, we found that the expression of AR3, a major AR splice variant that lacks the AR ligand-binding domain, was substantially increased after castration resistance development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 26 publications
3
95
0
Order By: Relevance
“…We noticed that although both Casodex and MDV3100 have significant anti-growth effects in LNCaP, C81, and C4-2 cells, both anti-androgen drugs showed less effect on CWR22Rv1 cell growth, which could be due to the existence of the AR variant, AR3, (27,38). Recent reports have documented that Casodex failed to suppress AR3 transactivation, and this is probably due 6 ) were mixed with Matrigel and injected into both anterior prostates of nude mice.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…We noticed that although both Casodex and MDV3100 have significant anti-growth effects in LNCaP, C81, and C4-2 cells, both anti-androgen drugs showed less effect on CWR22Rv1 cell growth, which could be due to the existence of the AR variant, AR3, (27,38). Recent reports have documented that Casodex failed to suppress AR3 transactivation, and this is probably due 6 ) were mixed with Matrigel and injected into both anterior prostates of nude mice.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, Hu et al (39) also found in both in vitro and in vivo studies that MDV3100 or abiraterone treatment increased AR3 expression, which might then enhance cell cycle-related genes to promote PCa progression. In contrast, ASC-J9 could degrade both full-length AR and AR3 (27), providing another explanation of why ASC-J9 showed better therapeutic effects in battling both PCa cell growth and metastasis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Notably, telomere dysfunction and the activation of ATM kinase by AR inactivation also occurs in AR-positive castration-resistant 22Rv1 cells (Fig. 1F) that are resistant to the growth inhibitory effect of AR antagonists such as Casodex (34). This suggests that telomere dysfunction and FIGURE 1.…”
Section: Ar Inactivation-induced Telomere Dysfunction Triggersmentioning
confidence: 93%